Dose-rate estimation using α-Al2O3:C chips: aftermath - Kreutzer, Sebastian; Tribolo, Chantal; Martin, Loïc; Mercier, Norbert (Ancient TL, 2020)
We present additional experiments for αAl2O3:C chips used to estimate in situ γ-dose rates. Our contribution supplements the article by Kreutzer et al. (2018) and presents results from previously announced follow-up experiments. (1) We investigate the divergent γ-dose rate results we obtained from cross-check experiments for one reference site. (2) We discuss the origin of encountered large inter-aliquot scatter using results from low-level background and calibration measurements. (3) We show that the chip geometries vary considerably, which may partly contribute to additional inter-aliquot scatter, regardless of an overall good reproducibility of results. (4) We report new source-calibration results after replacing the β-source housing of our measurement system, which resulted in an increase of the source dose rate at the sample position by ca 37%. GEANT4 simulations show that the increased dose rate is likely caused by an unfortunate fabrication tolerance of the shutter in front of the β-source, which, in combination with the chip geometry, significantly contributes to the observed inter-aliquot scatter. (5) Finally, we introduce a newly developed shiny application we use at the IRAMAT-CRP2A to analyse α-Al2O3:C measurements. The application is open-source and freely available.
Im Titel sind die Zahlen 2 und 3 jeweils tiefgestellt
Gesehen am 27.03.2025